The hepatitis B core antibody positive/hepatitis B surface antigen negative pattern is associated with the increased risk of intracranial atherosclerotic stenosis - Shen, Lin (Medicine (Baltimore), 2020)
The high prevalence of hepatitis B virus (HBV) infection and intracranial atherosclerotic stenosis (ICAS) in Asia raises the question as to whether HBV infection is associated with ICAS. To answer this question, we tested the association between HBV infection and ICAS. Totally, 3072 in-hospital subjects were retrospectively enrolled. All subjects underwent computed tomography angiography (CTA) and serological testing for HBV infection. Based on the results of CTA, all subjects were categorized into 4 groups including ICAS, extracranial atherosclerotic stenosis (ECAS), ICAS/ECAS (both ICAS and ECAS), and normal. HBV infection was divided into 4 patterns including hepatitis B core antibody (anti-HBc) positive/hepatitis B surface antigen (HBsAg) positive, anti-HBc-positive/HBsAg-negative, anti-HBc-negative/HBsAg-positive, and anti-HBc-negative/HBsAg-negative. Risk factors for atherosclerosis were collected based on medical records. Multiple logistic regression models were used to determine the association between infection patterns and ICAS. We found that the anti-HBc-positive / HBsAg-negative pattern was associated with the increased risk of ICAS (OR = 1.462) and not associated with ECAS or ICAS / ECAS. The HBc-positive/HBsAg-positive pattern was not associated with ICAS, ECAS or ICAS/ECAS. In conclusions, the anti-HBc-positive/HBsAg-negative pattern was associated with the increased risk of ICAS. Anti-HBc should be employed to investigate the association between HBV infection and cerebrovascular diseases.